2002
DOI: 10.1046/j.1540-8167.2002.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thoracic Spinal Cord Stimulation on Cardiac Autonomic Regulation of the Sinus and Atrioventricular Nodes

Abstract: SCS appears to enhance parasympathetic activity, mediated via the vagus. This may have implications for use of thoracic SCS to treat chronic angina and perhaps prevent sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 6 publications
1
48
1
Order By: Relevance
“…These changes would suggest a predominantly sympathetic effect of SCS in the atria. However, one important difference in this study as compared with the Olgin et al 54 study is that Bernstein et al 55 applied SCS from T1-T5 whereas Olgin et al applied SCS to T1-T2. Therefore, it is possible that different populations of nerves were recruited with SCS in the two studies, which could have influenced the net effect of SCS stimulation.…”
Section: Spinal Cord Stimulation Spinal Cord Stimulation and Atrial Ementioning
confidence: 75%
See 2 more Smart Citations
“…These changes would suggest a predominantly sympathetic effect of SCS in the atria. However, one important difference in this study as compared with the Olgin et al 54 study is that Bernstein et al 55 applied SCS from T1-T5 whereas Olgin et al applied SCS to T1-T2. Therefore, it is possible that different populations of nerves were recruited with SCS in the two studies, which could have influenced the net effect of SCS stimulation.…”
Section: Spinal Cord Stimulation Spinal Cord Stimulation and Atrial Ementioning
confidence: 75%
“…SCS in dogs applied at the T1-T2 level prolonged sinus cycle length and increased AH interval conduction time, which was abolished by vagotomy, suggesting that SCS at T1-T2 has a predominantly vagal effect. 54 However, a recent study by Bernstein et al 55 applied SCS to a canine model of AF induced by rapid atrial pacing, and showed that SCS prolonged the atrial effective refractory periods in both atria and reduced AF inducibility if SCS was applied at the time that rapid atrial pacing began. These changes would suggest a predominantly sympathetic effect of SCS in the atria.…”
Section: Spinal Cord Stimulation Spinal Cord Stimulation and Atrial Ementioning
confidence: 99%
See 1 more Smart Citation
“…102 There is basic evidence that SCS enhances the vagal tonus. 103 In concert with this observation, a study in patients with severe coronary artery disease demonstrates that vagal stimulation, inhibiting norepinephrine release from sympathetic nerves to the heart, may subsequently alter the sympatholytic/ vagotonic balance and so dilates cardiac microcirculatory vessels. 104 Mannheimer and coworkers put forward the hypothesis that electrical neuromodulation reduces the myocardial oxygen demand.…”
Section: Electrical Neuromodulation and Myocardial Ischemiamentioning
confidence: 96%
“…These effects were abolished after transection of bilateral cervical vagus nerves but not transection of ansae subclaviae (sympathectomy), suggesting the effect of SCS is vagally mediated. 12 In a canine model of ischemic HF, SCS during transient myocardial ischemia reduced the incidence of spontaneous ventricular tachyarrhythmias. 13 This antiarrhythmic effect was again associated with vagal effects -reduction in sinus rate, prolongation of PR interval and lowering of blood pressure.…”
Section: Preclinical Researchmentioning
confidence: 99%